Effectiveness of indigenous plant powders as grain protectant against Callosobruchus chinensis (L.) in stored chickpea (Cicer arietinum) (Bangladesh Journal of Agricultural Research, 2014)
The effectiveness of 17 indigenous plant powders as grain protectant were assessed against Callosobruchus chinensis (L.). The results indicated that among all the tested plant materials, tobacco leaf powder (TLP) had promising effects on inhibiting oviposition and reducing adult emergence, seed infestation, and weight loss by C. chinensis. Tobacco leaf powder offered complete protection of chickpea seeds applied at 20.0 g/kg seeds. Its lower doses exhibited efficacy in dose dependant manner. The lowest number of eggs (24.60), egg bearing seeds (23.40), adult emergence (23.20), seed infestation (8.28%), and weight loss (0.50%) were obtained from the TLP treated at 10.0 g/kg seeds, while the highest of these parameters were in untreated control. In the ovicidal test, TLP showed 100% inhibition at 20.0 g/kg seeds over control. The lowest number of adults (37.20) were emerged when larvae bearing seeds were treated with TLP at 20.0 g/kg seeds along with 59.39% retardation over the control and had no adverse effect on seed germination up to 3 months. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20146 Bangladesh J. Agril. Res. 39(1): 93-103, March 2014